Current situation of judicial reform in Ukraine: problems and ways of their solution - Bandurka, O. M.; Бандурка, О. М.; Teremetskyi, V. I.; Теремецький, В. І.; Boiko, V.; Zubov, O.; Patlachuk, V. (Lex Humana. – 2023. – Vol. 15, № 4 . – P. 55-72, 2023)
Автори охарактеризували реформаційні процеси у сфері юстиції, які останнім часом відбуваються в Україні. Проаналізовано основні завдання, визначені Стратегією розвитку системи правосуддя та конституційного судочинства на 2021-2023 роки.

The authors have characterized reformation processes in the justice sphere, which have been recently taking place in Ukraine. The main objectives identified in the Strategy for the Development of the Justice System and Constitutional Judiciary for 2021-2023 have been analyzed. The main obstacles affecting the processes of improving the functioning of the judicial power and the administration of justice have been established. The problems that arise during the implementation of the main provisions of the Strategy for the Development of the Justice System have been identified. Examples of controversial draft laws that negatively affect judicial reform in general and the stability of the judicial system in particular have been provided. It has been asserted that the main purpose of certain draft laws is to gain control over a part of the judicial system, which negatively affects the improvement of the courts activities and the development of the judiciary. The authors have studied the main problems that determine the need for further improvement of the functioning of the judicial power and the administration of justice, as well as have offered the ways of their elimination

Авторы охарактеризовали реформационные процессы в сфере юстиции, которые в последнее время проходят в Украине. Проанализированы основные задачи, определенные Стратегией развития системы правосудия и конституционного судопроизводства на 2021-2023 годы.

Os autores caracterizaram os processos de reforma na esfera da justiça que vêm ocorrendo recentemente na Ucrânia. Foram analisados os principais objetivos identificados na Estratégia para o Desenvolvimento da Justiça e da Magistratura Constitucional para 2021-2023. Foram identificados os principais obstáculos que afetam os processos de melhoria do funcionamento do poder judiciário e da administração da justiça. Foram identificados os problemas que surgem durante a implementação das principais disposições da Estratégia para o Desenvolvimento do Sistema de Justiça. Exemplos de projetos de lei controversos que afetam negativamente a reforma judicial em geral e a estabilidade do sistema judicial em particular foram fornecidos. Tem sido afirmado que o principal objetivo de certos projetos de lei é obter controle sobre uma parte do sistema judicial, o que afeta negativamente a melhoria das atividades dos tribunais e o desenvolvimento do judiciário. Os autores estudaram os principais problemas que determinam a necessidade de maior aperfeiçoamento do funcionamento do poder judiciário e da administração da justiça, bem como ofereceram as formas de sua eliminação.
O estado atual da reforma judicial na Ucrânia: problemas e formas de os resolver
Keywords: Ukraine; publikatsii u WoS; Україна; judicial reform; judicial system; courts; justice; evaluation of court activities; public control; судова реформа; судова система; суд; справедливість; оцінка діяльності суду; громадський контроль; судебная реформа; судебная система; справедливость; оценка деятельности суда; общественный контроль